Consumer Protection against Imported Cosmetic Products that Have Not Been Certified by The Indonesian Food and Drug Authority on Tokopedia Platform - Luthfia Nurhaliza Wirawan; Moh. Indra Bangsawan; Bambang Sukoco; Muhammad Safrizal; R Rahmawani; R Ramadani (Universitas Muhammadiyah Surakarta, 2025)
E-commerce platforms in Indonesia have made it easier for consumers to access various products through an application, including imported cosmetic products. However, many imported cosmetic products that have not been certified by the Indonesian Food and Drug Authority (BPOM) continue to circulate on the Tokopedia platform, posing a risk to consumers. This research aims to find out: 1) Regulations governing the circulation of imported cosmetics in Indonesia, and 2) Consumer protection against illegal cosmetic products on Tokopedia. This research uses a normative juridical method with a qualitative approach that focuses on analyzing laws and regulations and case studies. The data used consists of primary data, namely Law No. 8 of 1999 on Consumer Protection, Law No. 11 of 2008 in conjunction with Law No. 1 of 2024 on Electronic Information and Transactions, and Regulation of the Indonesian Food and Drug Authority No. 12 of 2023 on the Supervision of the Manufacture and Distribution of Cosmetics, while secondary data includes journals and cases related to cosmetics without Indonesian Food and Drug Authority certification on e-commerce platforms. Data collection is done through literature study and legal document analysis. Furthermore, the data was analyzed using descriptive qualitative analysis method to interpret the regulations and literature study. The results show that although regulations related to consumer protection and electronic commerce already exist, their implementation still faces various obstacles. Consumers have the right to obtain safe and legal products, but supervision of products in e-commerce is still weak. Tokopedia as a marketplace organizer has a role in filtering products that are traded, but it has not been fully effective in suppressing the circulation of illegal imported cosmetics. Therefore, it is necessary to strengthen regulations, increase supervision, and the active role of e-commerce platforms in maintaining consumer safety.